Assessment of satellite-based aerosol optical depth using continuous lidar observation. (September 2016) - Lin, C.Q.; Li, C.C.; Lau, A.K.H.; Yuan, Z.B.; Lu, X.C.; Tse, K.T.; Fung, J.C.H.; Li, Y.; Yao, T.; Su, L.; Li, Z.Y.; Zhang, Y.Q.
Abstract: Due to a reliance on solar radiation, the aerosol optical depth (AOD) is observed only during the day by passive satellite-based instruments such as the MODerate resolution Imaging Spectroradiometer (MODIS). Research on urban air quality, atmospheric turbidity, and evolution of aerosols in the atmospheric boundary layer, however, requires 24-h measurement of aerosols. A lidar system is capable of detecting the vertical distribution of the aerosol extinction coefficient and calculating the AOD throughout the day, but routinely lidar observation is still quite limited and the results from MODIS and lidar sometimes are contradictory in China. In this study, long-term lidar observations from 2005 to 2009 over Hong Kong were analyzed with a focus on identification of the reasons for different seasonal variation in the AOD data obtained from MODIS and lidar. The lidar-retrieved AOD shows the lowest average level, but has the most significant diurnal variation during the summer. When considering only a 5-h period between 10:00 a.m. and 3:00 p.m. local time to match satellite passages, the average of the lidar-retrieved AOD doubles during the summer and exceeds that during the winter. This finding is consistent with the MODIS observation of a higher AOD during the summer and a lower AOD during the winter. The increase in the aerosol extinction coefficient in the upper level of the mixing layer makes the greatest contribution to the increase in the AOD at midday during the summer. These assessments suggest that large over-estimation may occur when long-term averages of AOD are estimated from passive satellite observations. Highlights: 5-year continuous lidar measurements were used to assess the satellite-based AOD. Different seasonal variation in AOD is observed by MODIS and lidar over Hong Kong. Aerosols in the upper mixing layer largely increase AOD at midday during summer. Long-term average of AOD, estimated from satellite observation, may has large error.